Can an Asia Pacific Community, similar to the European Community, emerge? - Moshirian, Fariborz (Journal of Banking & Finance, 2009)
The purpose of this paper is to analyse whether the Asia Pacific region could form a union similar to the one now established in Europe. To this end, it analyses some of the major challenge faced by the US prior to its union in the 19th century and the way countries such as France and Germany contributed to the formation of the EU, despite their past animosity. The paper proposed a two tier system for the emergence of a union in the Asia Pacific region in which all countries could become part of a regional framework for regional security and free trade and some of the more advanced countries in the region could start the process of financial integration and invite other member countries to join them over time. The paper argues that in the 2st century, unlike the claim of the “currency optimum theory,” there is no need for labour mobility amongst Asian countries for the formation of a union in this region and hence Australia should not expect millions of workers from China to migrate there. The paper argues that the role of Japan and China in the process of regional integration has been underestimated, due to the claim that the former is a monoculture and the latter is too nationalistic. The paper highlights how diversity in the region could be seen as a strength in the Asia Pacific region. It also shows how the process of globalisation has already overcome differences in culture, religion and race which used to be stumbling blocks for more regional or global integration. The paper argues that a union in the Asia Pacific region would reduce “home bias” for international capital flows and hence there would be significant financial transformation of countries in this region.